2011
DOI: 10.1016/j.cardfail.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Red Cell Distribution Width (RDW) in Cardiorenal Patients: RDW is Not Related to Erythropoietin Resistance

Abstract: EPO resistance was not associated with RDW. RDW was associated with functional iron availability, erythropoietic activity, and interleukin-6 in anemic patients with CHF and CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 33 publications
(50 reference statements)
3
49
1
1
Order By: Relevance
“…15,20,21) However, it has already been concluded that RDW predicts poor long-term outcome regardless of anemia status in AHF patients. 14,22,23) We observed that RDW was associated with low hemoglobin and depressed MCV, which are consistent with a state of impaired iron mobilization. RDW was an independent predictive factor after adjustment for hemoglobin in short-term outcome, though it had limitations in predicting 30-day clinical outcome.…”
Section: Discussionsupporting
confidence: 74%
“…15,20,21) However, it has already been concluded that RDW predicts poor long-term outcome regardless of anemia status in AHF patients. 14,22,23) We observed that RDW was associated with low hemoglobin and depressed MCV, which are consistent with a state of impaired iron mobilization. RDW was an independent predictive factor after adjustment for hemoglobin in short-term outcome, though it had limitations in predicting 30-day clinical outcome.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have demonstrated a relationship between RDW and indicators of inflammation such as erythrocyte sedimentation rate, high sensitivity C-reactive protein, fibrinogen, interleukin-6, soluble tumor necrosis factor (TNF) receptor I and soluble TNF receptor II [23,26,27]. Additionally, chronic inflammation leads to disturbances in iron metabolism and an impaired bone marrow response to erythropoietin, increasing the RDW value [27,28]. Chronic inflammation is often observed in patients with chronic kidney disease [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammation may contribute to increased RDW values by inhibiting responses to erythropoietin or the production of erythropoietin and shortening red blood cell survival [20]. Additionally, although Forthecz et al [21] associated this situation with erythropoietin resistance, Emans et al [22] related it to ineffective erythropoiesis formed by erythropoietic activity and increased erythrocyte destruction, claiming that it is not related to erythropoietin resistance. In this study, patients with schizophrenia had significantly higher RDW values compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%